Exploring the Combined Impact of Probiotics and Organic Acids as Alternatives to Antibiotics on Gut Microbiome Balance and Disease Resistance in Broilers: A Randomized Controlled Trial - Younis, Waqar; Khan, Nazima Yousaf; Tanveer, Farah; Khan, Muhammad Asfandyar; Tayyab, Muhammad; Aziz, Tariq; Alam, Hafiz Munsif; Iqbal, Maryam; Tariq, Mehran; Adrian Shah, Shahzada Khurram (Indus Journal of Bioscience Research, 2025)
The overutilization of antibiotic growth promoters in chicken production has contributed to the global challenge of antimicrobial resistance, necessitating the immediate development of sustainable and effective alternatives. Natural feed additives, including probiotics and organic acids, have attracted interest for their ability to improve intestinal health, immunity, and performance in broilers, without the negative consequences of antibiotics. This study examined the combined effects of probiotics and organic acids on the stability of the gut microbiome and disease resistance in broiler chickens under controlled experimental circumstances. This study aimed to assess the efficacy of a combination of probiotics and organic acids as a potential substitute for antibiotics in enhancing the growth performance and intestinal health of broilers. A randomized controlled trial was performed University of Veterinary and Animal Sciences, Lahore, Pakistan, with 600 Cobb 500 broiler chicks divided into five dietary groups: negative control, antibiotic control, probiotic-only group, organic acid-only group, and combined probiotic-organic acid group. Birds were observed over a 42-day period for performance measures (body weight gain, feed conversion ratio, and average daily gain), microbiome diversity (via 16S rRNA sequencing), and illness resistance after a Salmonella enterica challenge on day 21. Statistical analyses were performed using ANOVA and PERMANOVA. The findings demonstrated that the combined group surpassed all other treatments, exhibiting much greater weight gain (2000 g), improved feed conversion ratio (FCR: 1.65), reduced mortality (1%), and increased microbial diversity (Shannon Index: 4.0). These data validate the concept that synergistic supplementation provides enhanced advantages over individual additives or antibiotics. This study presents substantial evidence that the integration of probiotics and organic acids improves broiler health and performance, signifying a viable approach for antibiotic-free poultry production. These results will enhance sustainable animal husbandry and provide practical guidance for feed formulation and policy creation.